PENGARUH ASAS TRILOGI KEPEMIMPINAN DAN AKSEBILITAS LAPORAN KEUANGAN TERHADAP PENERAPAN TRANSPARANSI PELAPORAN KEUANGAN - Ayem, Sri; Enumbi, Misra (Program Studi Akuntansi Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2024)
This research aims to examine and analyze the influence of the Leadership Trilogy Principle and Accessibility of Financial Reports on the Implementation of Financial Reporting Transparency in SKPDs in the Yogyakarta Special Regional Government. The population of this study consisted of 89 respondents, these 89 respondents were selected as research samples based on purposive sampling, so there were 89 research samples. The data analysis method used is multiple linear regression analysis. The research results show that the leadership trilogy has a positive effect on the transparency of financial reporting and the accessibility of financial reports also has a positive effect on the transparency of financial reporting